(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This article provides a comprehensive analysis of the crisis in interethnic relations that emerged in Uzbekistan in the late 1980s, on the eve of independence. It explores the decline of attention to national issues during the final years of the Soviet period, the socio-economic tensions, migration processes, and the consequences of the artificially promoted multiethnic policy. Using the example of the 1989 Fergana events, the article examines the roots of interethnic conflicts, the measures taken to overcome them, and the political and ideological steps implemented under the leadership of the First President, Islam Karimov. The study also highlights the historical lessons related to ensuring interethnic harmony, tolerance, and strengthening traditions of mutual respect in society.